Analytical chemistry for technicians - Kenkel, John. (Boca Raton : CRC Press/Taylor & Francis, 2014)
'This thoroughly updated fourth edition is designed to be a powerful training tool for entry-level chemistry technicians. This book explains analytical chemistry and instrumental analysis principles and how to apply them in the real world. Over 50 updated workplace scene sidebars with stories and photographs of technicians and chemists working with the equipment or performing the techniques discussed in the text brings the workplace of the chemical technician into the classroom. In addition, supplemental material is now available for download on the web. The text includes more than 60 experiments specifically relevant to the laboratory technician, along with questions and problems in each chapter'--
Includes bibliographical references and index.
Keywords: Chemistry, Analytic